Influence of mesoscale eddies on Indonesian throughflow dynamics in the Sulawesi Sea simulated in an ocean general circulation model - Fuad Azminuddin; Adi Purwandana; Aloysius Bagyo Widagdo; Mardi Wibowo; Raden Dwi Susanto (Progress in Oceanography, 2026)

Where waters transform: Hydrographic variability and turbulent mixing in the lifamatola passage, Indonesia - Adi Purwandana; Zheng Wang; Rui Li; Zhenhua Xu; Yao Li; Dewi Surinati; Fuad Azminuddin; Bayu Priyono; Dwiyoga Nugroho; Muhammad R. Cordova; Teguh Agustiadi; Mochamad R. Iskandar; et al. (Progress in Oceanography, 2026)

Historical characteristics and climate mode modulation of extreme wave climate over Indonesian Maritime continent based on ERA5 reanalysis data - Ahmad Bayhaqi; Mochamad Riza Iskandar; Fuad Azminuddin; Saat Mubarrok; Muhammad Iqbal; Dewi Surinati; Faizal Ade Rahmahuddin Abdullah (Climate Dynamics, 2026)

Coastal erosion in Eastern Bali: impacts of the Indonesian throughflow - Fuad Azminuddin; Aloysius Bagyo Widagdo; Mardi Wibowo; Hanah Khoirunnisa; Reno Arief Rachman; Hamzah Haru Radityo Suharyanto (Natural Hazards, 2026)

Assessment of thermocline depth bias in the Seychelles-Chagos Thermocline Ridge of the Southwestern Indian Ocean simulated by the CMIP6 models - Saat Mubarrok; Fuad Azminuddin; Chan Joo Jang (Frontiers in Marine Science, 2023)
The Seychelles-Chagos Thermocline Ridge (SCTR, 5°S-10°S, 50°E-80°E) is a unique open-ocean upwelling region in the southwestern Indian Ocean. Due to the negative wind stress curl between the equatorial westerlies and southeasterly trade winds, SCTR is known as a strong upwelling region with high biological productivity, providing a primary fishing zone for the surrounding countries. Given its importance in shaping the variability of the Indian Ocean climate by understanding the sea-air interaction and its dynamics, the simulation of SCTR is evaluated using outputs from the Coupled Model Intercomparison Project Phase Sixth (CMIP6). Compared to observations, 23 out of 27 CMIP6 models tend to simulate considerably deeper SCTR thermocline depth (defined as the 20°C isotherm depth (D20))– a common bias in climate models. The deep bias is related to the easterly wind bias in the equatorial to southern Indian Ocean, which is prominent in boreal summer and fall. This easterly wind bias produces a weak annual mean Ekman pumping, especially in the boreal fall. Throughout the year, the observed Ekman pumping is positive and is driven by two components: the curl term, is associated with the wind stress curl, leads to upwelling during boreal summer to fall; the beta term, is linked to planetary beta and zonal wind stress, contributes to downwelling during boreal spring to fall. However, the easterly wind bias in the CMIP6 increases both the positive curl and negative beta terms. The beta term bias offsets the curl term bias and reduces the upwelling velocity. Furthermore, the easterly wind bias is likely caused by the reduced east-west sea surface temperature (SST) difference associated with a pronounced warm bias in the western equatorial Indian Ocean, accompanied by the east-west mean sea level pressure gradient over the Indian Ocean. Furthermore, this study finds local wind-induced Ekman pumping to be a more dominant factor in thermocline depth bias than Rossby waves, despite CMIP6 models replicating Rossby wave propagation. This study highlights the importance of the beta term in the Ekman pumping simulation. Thus, reducing the boreal summer-to-fall easterly wind bias over the Indian Ocean region may improve the thermocline depth simulation over the SCTR region.

Destination of New Guinea Coastal Undercurrent in the western tropical Pacific: Variability and linkages - Fuad Azminuddin; Chan Joo Jang; Dongchull Jeon (Frontiers in Marine Science, 2022)
The New Guinea Coastal Undercurrent (NGCUC) is considered a bottleneck in the western tropical Pacific (WTP), carrying upper-to-intermediate waters from the south to the northwestern Pacific, thereby playing a fundamen tal role in the interhemispheric water mass exchange. However, how the NGCUC links to the circulation in the WTP was insufficiently studied. This work explores the destination of NGCUC waters, its spatiotemporal changes, and possible physical processes linked with the downstream NGCUC using ocean reanalysis for 22 years (1994 – 2015). Lagrangian particle tracking discloses eight major destinations of the NGCUC: The Equatorial Undercurrent (EUC, 35.26%), the North Equatorial Countercurrent (NECC, 12.3%), the North (13.33%) and South (8.85%) Subsurface Countercurrents, the Equatorial Deep Jet (11.49%), the Mindanao Undercurrent (13.24%), and the Indonesian (3.47%) and Halmahera (0.86%) Throughflows. The NGCUC waters are distributed mainly to the east (81.65%) and their dissemination varies markedly with depth. These destinations exhibit significant variations on seasonal and interannual time scales. The NGCUC strengthens (weakens) during summer (winter) and more NGCUC waters are distributed westward and northeastward (eastward). Interannually, the distribution of the NGCUC water is influenced by El Niño-Southern Oscillation, in which most of its eastward-distributed waters shift northward (equatorward) in El Niño (La Niña) phase joining the strengthened NECC (EUC). Changes in the NGCUC water destination can transform the water mass properties in the WTP. The findings of this study also emphasize the fundamental role of eddies in trapping and redistributing the NGCUC waters and linking the currents in the WTP.

Intraseasonal-to-Interannual Variability of the Upper-Layer Zonal Currents in the Tropical Northwest Pacific Ocean - Fuad Azminuddin; Dongchull Jeon; Chang-Woong Shin (Ocean Science Journal, 2019)